Trimetazidine inhibits liver fibrosis and hepatic stellate cell proliferation and blocks transforming growth factor-β (TGFβ)/Smad signaling in vitro and in vivo. Issue 3 (1st March 2022) - Ding, Wenwen; Zhou, Danhua; Zhang, Shimeng; Qian, Jiaping; Yang, Lingxia; Tang, Lei
ABSTRACT: Trimetazidine (TMZ) has been used extensively to treat coronary artery disease and to reduce fibrosis. Liver fibrosis is a reversible process. However, the impacts of TMZ on liver fibrosis triggered by CCl4 and on hepatic stellate cells in liver fibrosis remain to be elaborated. In the current study, the liver fibrosis models were constructed by using CCl4 -induced mice and TGF-β-induced hepatic stellate cells. The involvement of TMZ in liver fibrosis was subsequently investigated. In the CCl4 -induced hepatic fibrosis mouse model, it was shown that the expression levels of alanine aminotransferase and aspartate aminotransferase were reduced after TMZ treatment; the expression levels of the extracellular matrix proteins colla1 and α-SMA were down-regulated; furthermore, the expression levels of TGFβ/Smad signaling proteins were inhibited. In TGF-β-induced hepatic stellate cells, compared to the TGF-β-induced group, cell proliferation and migration were inhibited after TMZ treatment; meanwhile, extracellular matrix protein and TGFβ/Smad signaling protein expression levels followed the same trend as in the hepatic fibrosis model. In conclusion, TMZ could block the TGFβ/Smad signaling in liver fibrosis model, with inhibiting liver fibrosis and hepatic stellate cell proliferation. This may broaden the application sphere of TMZ in liver fibrosis therapy. Graphical abstract: uf0001